High resolution characterization of sulfur-assisted degradation in alloy 800. (1st August 2018) - Persaud, S.Y.; Long, F.; Korinek, A.; Smith, J.M.
Highlights: EAC, IGC, and pitting occurred in Alloy 800 exposed to a 280 °C acid-sulfate environment. Nano-scale chemical characterization at crack tips revealed mixed Ti- and Cr-rich oxide(s) with sulfur incorporated. Adsorption of sulfur leads to a poorly adherent mixed oxide/sulfide layer, propagating EAC via film-rupture. Nano-scale characterization of pits revealed a 10 nm thick sulfur layer and minimal oxides. Transition from EAC to pitting occurs at near-complete sulfur surface coverage, which limits oxide nucleation. Abstract: Environmentally assisted cracking (EAC) initiation tests were carried out by subjecting Alloy 800 tensile specimens to 0.55 mol/kg SO4 2− solution, pH280°C 3, at 280 °C using slow rise-time cyclic loading and in-situ crack detection. EAC, intergranular corrosion (IGC), and pitting were observed. Transmission electron microscopy analysis revealed Ti- and Cr-rich oxides in cracks, and sulfur incorporated in oxide(s) or as sulfide compound(s). This oxide/sulfide film is likely impaired, producing a slip dissolution-type EAC mechanism. For pitting, only a nano-scale sulfur layer was identified at pit-metal interfaces. This high surface coverage of adsorbed sulfur limited oxide nucleation and accelerated metal dissolution.